El género Cresera Schaus, 1894 (Lepidoptera: Arctiinae) en el Perú: diversidad y patrones de distribución geográfica - Grados, Juan (2017)
The genus Cresera Schaus, 1894 comprises 12 species, 8 of which occur in Peru. A recognition diagnosis based on wings coloring characters is given for the species on this genus as well as the geographic distribution patterns for Peru.